Konstruksi Realitas Binge-Watching Drama Korea dalam Pembentukan Pola Komunikasi Interpersonal Generasi Z (Studi Fenomenologi pada Remaja Akhir di Kompleks Bahagia Permai) - Aria Perbawa; Rodhiyat Fajar Salim; Imam Jahrudin Priyanto (Journal of Media and Communication | E-ISSN : 3063-9581, 2026)
Binge-watching is the activity of watching digital shows for extended periods continuously without interruption. This phenomenon is widely experienced by Generation Z, particularly older adolescents who integrate it into their digital lifestyle. This study aims to understand how the experience of binge-watching Korean dramas plays a role in shaping Generation Z's interpersonal communication patterns through the process of social construction of reality across externalization, objectivation, and internalization dimensions. This study utilizes a qualitative method with a phenomenological approach. The Social Construction of Reality Theory by Peter L. Berger and Thomas Luckmann is employed as the analytical framework. Data collection techniques included observation, in-depth interviews, and documentation involving six Generation Z older adolescents aged 18–24 in the Bahagia Permai Complex, Bandung, who actively engage in binge-watching Korean dramas. The results indicate that in the internalization dimension, informants absorb values, ideal relationship standards, and emotional regulation from Korean dramas into their subjective consciousness. In the objectivation dimension, a habituation of a new culture occurs within peer circles, such as the use of Korean terms and the tolerance of delayed message responses. Meanwhile, in the externalization dimension, this activity exerts a dual impact; it strengthens emotional closeness among fellow fans, yet triggers communication distortion in the form of decreased quality of face-to-face interaction, a state of mind immersed in the storyline (transportation effect), and the use of binge-watching as a passive-aggressive strategy to avoid real-world conflicts. This study concludes that the experience of binge-watching Korean dramas actively constructs a new reality and redefines the interpersonal communication patterns of older adolescents in the digital era.